Thermal Stability of Water Ice in Ceres' Craters: The Case of Juling Crater. Issue 9 (27th September 2018) - Formisano, M.; Federico, C.; De Sanctis, M. C.; Frigeri, A.; Magni, G.; Raponi, A.; Tosi, F.
Abstract: Ice thermal stability on the surface of the dwarf planet Ceres is an important issue linked to the Herschel observations of water vapor around Ceres. One of these surficial ice deposits is located within the 20‐km crater Juling (35°S, 168°E). The study of water ice exposure in this specific crater is particularly interesting because it has been observed that the water ice abundance changes on a time scale of a few months. To understand the ice behavior, we applied a 3‐D finite element method thermophysical model to the study of Juling crater in order to determine the water ice sublimation rate. We use a detailed shape model of Ceres derived from optical imagery returned by the Framing Camera on board Dawn. We explore the effects of different heliocentric distances and different thermal inertia values, comparing our numerical predictions with the observational evidences returned by VIR and by the Herschel Space Observatory. Plain Language Summary: Ceres is a dwarf planet of the solar system with a significant amount of water both in its interior and in the surface layers. A crater in the southern hemisphere, Juling, is characterized by the presence on its surface of a mixture of ice and rocks as revealed by recent VIR data from the Dawn spacecraft. This crater is a good place to preserve ice since it is poorly illuminated, particularly in the northern wall. Most important is the detection of ice variations on its wall during the Dawn visible and infrared mapping spectrometer observations. In this work we performed numerical simulations in order to evaluate temperatures and water ice sublimation rate, assuming reasonable values for the physical parameters, and to estimate the longevity of ice on the surface of Ceres. Key Points: Ice stability on the surface of the crater Juling is an issue closely related to the Herschel observations of water vapor around Ceres. We apply a 3-D thermophysical model with real topography in order to evaluate the surface temperatures and the ice sublimation rates Juling northern wall, due to its faint solar illumination, results to be a good place to host water ice